Flow Cytometry Combined With Single Cell Sorting to Study Heterogeneous Germination of Bacillus Spores Under High Pressure - Zhang, Yifan; Delbrück, Alessia I.; Off, Cosima L.; Benke, Stephan; Mathys, Alexander (Frontiers in Microbiology, 2020)
Isostatic high pressure (HP) of 150 MPa can trigger the germination of bacterial spores, making them lose their extreme resistance to stress factors, and increasing their susceptibility to milder inactivation strategies. However, germination response of spores within a population is very heterogeneous, and tools are needed to study this heterogeneity. Here, classical methods were combined with more recent and powerful techniques such as flow cytometry (FCM) and fluorescence activated cell sorting (FACS) to investigate spore germination behavior under HP. Bacillus subtilis spores were treated with HP at 150 MPa and 37°C, stained with SYTO16 and PI, and analyzed via FCM. Four sub-populations were detected. These sub-populations were for the first time isolated on single cell level using FACS and characterized in terms of their heat resistance (80°C, 10 min) and cultivability in a nutrient-rich environment. The four isolated sub-populations were found to include 1) heat-resistant and mostly cultivable superdormant spores, i.e. spores that remained dormant after this specific HP treatment, 2) heat-sensitive and cultivable germinated spores, 3) heat-sensitive and partially-cultivable germinated spores, and 4) membrane-compromised cells with barely detectable cultivability. Of particular interest was the physiological state of the third subpopulation, which was previously referred to as “unknown”. Moreover, the kinetic transitions between different physiological states were characterized. After less than 10 min of HP treatment, the majority of spores germinated and ended up in a sub-lethally damaged stage. HP treatment at 150 MPa and 37°C did not cause inactivation of all geminated spores, suggesting that subsequent inactivation strategies such as mild heat inactivation or other inactivation techniques are necessary to control spores in food. This study validated FCM as a powerful technique to investigate the heterogeneous behavior of spores under HP, and provided a pipeline using FACS for isolation of different sub-populations and subsequent characterization to understand their physiological states.